2021
DOI: 10.1186/s13613-021-00933-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ICU transfers on the mortality rate of patients with COVID-19: insights from comprehensive national database in France

Abstract: Background The first wave of the COVID-19 pandemic confronted healthcare systems around the world with unprecedented organizational challenges, particularly regarding the availability of intensive care unit (ICU) beds. One strategy implemented in France to alleviate healthcare pressure during the first COVID-19 wave was inter-hospital transfers of selected ICU patients from overwhelmed areas towards less saturated ones. At the time, the impact of this transfer strategy on patient mortality was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…They did not consider the DROM departments, which experienced a much different epidemic dynamic compared to mainland France, as shown in the present study. Furthermore, due to the real-time functioning of the SI-VIC database [28] , there were few retrospective corrections (e.g., adding missing cases having occurred prior to March). By contrast, in the PMSI database each hospital was asked to retrospectively review possible COVID cases and to add the appropriate CIM-10 identification codes.…”
Section: Discussionmentioning
confidence: 99%
“…They did not consider the DROM departments, which experienced a much different epidemic dynamic compared to mainland France, as shown in the present study. Furthermore, due to the real-time functioning of the SI-VIC database [28] , there were few retrospective corrections (e.g., adding missing cases having occurred prior to March). By contrast, in the PMSI database each hospital was asked to retrospectively review possible COVID cases and to add the appropriate CIM-10 identification codes.…”
Section: Discussionmentioning
confidence: 99%
“…As the authors notice, the main result is somewhat surprising as higher mortality has not been reported in recent literature [ 2 , 3 ]. Reasons could be explained as follow: first, the authors specify that 20% of capacity transfers occurred at night, involving severe critically ill patients with acute lung injury, sepsis, and cardiogenic shock.…”
mentioning
confidence: 83%
“…Assuming that interhospital transfers are unsafe and choosing a strategy of implementation of new ICU beds to face surge of critically ill patients could lead to a higher mortality [ 7 ]. During the first months of the COVID-19 crisis, countries planned and organized large-scale interhospital transfers either for clinical or capacity reasons and demonstrated that transferred patients did not have a higher mortality rate [ 2 , 3 , 8 ]. However, we agree with the authors and acknowledge that “understanding the impact of ICU-to-ICU transfer on patient outcome is complex and must consider a couple of important aspects” such as identifying appropriate control patients.…”
mentioning
confidence: 99%
“… 18 Another study of a national French database suggests that mortality in transferred patients is lower, albeit with no standardisation of patient baseline characteristics. 19 When corrected for comorbidities and disease severity, a cross-sectional study of all public and private hospitals in France still found lower intensive care unit mortality in patients that underwent inter-regional transfer. 20 Aside from the French data, there is early evidence from a retrospective review in the United States that critical care transport was associated with few adverse events and similar mortality to patients in other COVID-19 studies.…”
Section: Introductionmentioning
confidence: 99%